Nanopore-based targeted sequencing test for direct tuberculosis identification, genotyping, and detection of drug resistance mutations: a side-by-side comparison of targeted next-generation sequencing technologies - Cabibbe, Andrea Maurizio; Moghaddasi, Kiarash; Batignani, Virginia; Morgan, Godstime Stephen Kojo; Di Marco, Federico; Cirillo, Daniela Maria (Journal of clinical microbiology, 2024)
We investigated the performance of the targeted next-generation sequencing (tNGS)-based Oxford Nanopore Diagnostics AmPORE TB assay, recently approved by the World Health Organization (WHO) as tuberculosis (TB) diagnostic test for the detection of drug resistance on respiratory specimens. A total of 104 DNA samples from Xpert MTB/RIF-positive TB sputum specimens were tested using the AmPORE TB kit, with the GenoScreen Deeplex Myc-TB as a comparative tNGS assay. For AmPORE TB, DNA samples were divided into five sequencing runs on the MinION device. Data analysis was performed using proprietary software. The WHO catalog of mutations was used for drug resistance interpretation. The assay achieved a high validity rate of 98% (102/104 DNA samples), homogeneous mean reads coverage across TB-positive specimens, and 100% positive and negative agreements for detecting mutations associated with resistance to rifampicin, pyrazinamide, fluoroquinolones, ethambutol, and capreomycin compared with Deeplex Myc-TB. The main discrepancies for the remaining drugs were attributable to the different assay panel designs. The AmPORE TB turnaround time was approximately 5-6 hours from extracted DNA to tNGS reporting for batches of 22 DNA samples. The AmPORE TB assay drastically reduced the time to tNGS reporting from days to hours and showed good performance for drug-resistant TB profiling compared with Deeplex Myc-TB. Targeted next-generation sequencing (tNGS) of provides comprehensive resistance predictions matched to new multidrug-resistant/rifampicin-resistant tuberculosis regimens and received World Health Organization approval for clinical use in respiratory samples in 2024. The advanced version of the Oxford Nanopore Diagnostics AmPORE TB tNGS kit was evaluated in this study for the first time and demonstrated good performance, flexibility, and faster turnaround time compared with the existing solutions.